Guidelines for handling multidimensionality in a terminological knowledge base. - Bowker, Lynne (University of Ottawa (Canada), 1992)
The goal of this thesis is to develop and apply a set of guidelines for handling multidimensionality in a terminological knowledge base (TKB). A dimension represents one way of classifying a group of objects; a classification with more than one dimension is said to be multidimensional. The recognition and representation of multidimensionality is a subject that has received very little attention in the terminology literature. One tool for dealing with multidimensionality is CODE (Conceptually Oriented Description Environment). This thesis is divided into four main parts. In Part I, we discuss the general principles of classification, and explain multidimensionality. In Part II, we develop an initial set of guidelines to help terminologists both recognize and represent multidimensionality in a TKB. In Part III, we develop a technical complement to the initial guidelines. We begin with a general description of the CODE system, and then we analyze those features that are particularly helpful for handling multidimensionality. Finally, in Part IV, we apply our guidelines by using the CODE system to construct a small TKB for concepts in a subfield of hypertext, namely hypertext links. (Abstract shortened by UMI.)
Keywords: Artificial Intelligence.